Adult mortality decline in Costa Rica - Rosero Bixby, Luis (1996)
Costa Rica is, along with Cuba, the country with the best health indicators in Latin America. Life expectancy at birth in Costa Rica was 77.9 years for women and 72.7 years for men in 1990, figures which are comparable with those for Western Europe and the USA. Study of the epidemiologic transition in Costa Rica has usually focused on children, reflecting the fact that the main component of mortality decline has been the prevention and control of premature deaths (Behm, 1976; Rosero-Bixby, 1986; CELADE et al., 1987; Cervantes and Raabe, 1991). The greater availability of information on child health and the young age structure of the population (in 1960, 47 per cent of the population were children under 15 years of age) have reinforced the emphasis on studying the young. This chapter shifts the previous emphasis on childhood to focus on adult mortality. The purpose is to describe the mortality transition at adult ages, to identify its key components, and to make inferences about its likely determinants. The chapter has five sections: socio-economic and public-health background of Costa Rica; the data and methods used; decline in risks of dying in two age intervals (20-49 and 50-79 years); analysis of risks of dying by cause of death; and areal analysis of adult mortality and its correlate across 100 small geographical units.